The Effect Of Education Level On Employee Performance With Competence As An Intervening Variable At The Mandailing Natal Regency Environmental Agency - Nur Azizah Matondang; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2025)
This study aims to examine the influence of education level on employee performance with competence as an intervening variable at the Mandailing Natal Regency Environmental Office. This study uses the Structural Equation Modeling (SEM) method with SmartPLS software to analyze data obtained from 71 employees at the Mandailing Natal Regency Environmental Office. The results of the analysis show that the level of education has a positive and significant influence on competence (T-Statistic = 40.493, P-Value = 0.000) and employee performance (T-Statistic = 4.456, P-Value = 0.000). In addition, competence is proven to have a significant influence on employee performance with a T-Statistic of 9.668 and a P-Value of 0.000. The resulting model showed an R-Square Adjusted value of 0.739 for the employee performance variable and 0.801 for the competency variable, which showed that 73.9% of the variation in employee performance could be explained by the model that included education level and competence, while 80.1% of the variation in competency could be explained by the level of education. Based on these findings, it can be concluded that the increase in education level contributes significantly to the improvement of employee competence and performance at the Mandailing Natal Regency Environmental Office. Therefore, it is recommended that the agency improve education and training programs for employees to improve competencies that will have an impact on improving overall performance.